Online Learning at the K-12 Level: An Examination of Teacher Technology Use by Subject Area and Grade Level - Sorensen, Chris (International journal of online pedagogy and course design, 2016)
Technology integration has had a profound effect on K-12 education with research yielding positive results in student learning. Most research to date has been conducted in face-to-face settings. With the growth of online K-12 learning, an opportunity exists to examine technology use in the “new” K-12 classroom. The aim of this research was to investigate the potential relationships between specific technology and subject area and grade level and why online K-12 teachers use technology in their online classrooms. Results suggest that in an online K-12 learning environment, relationships may exist between what technology is used and the subject area and/or grade level it is used in.